2020
DOI: 10.3389/frai.2020.559617
|View full text |Cite
|
Sign up to set email alerts
|

An Interpretable Predictive Model of Vaccine Utilization for Tanzania

Abstract: Providing accurate utilization forecasts is key to maintaining optimal vaccine stocks in any health facility. Current approaches to vaccine utilization forecasting are based on often outdated population census data, and rely on weak, low-dimensional demand forecasting models. Further, these models provide very little insights into factors that influence vaccine utilization. Here, we built a state-of-the-art, machine learning model using novel, temporally and regionally relevant vaccine utilization data. This h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…8 However, the real-world application of such analyses using AI technologies often focus on predictive model development, with a limited but emerging evidence-base deploying and scaling the models as effective and sustainable AI solutions in HIV programs. [9][10][11] There are few studies that examine the related use case of advanced analytics to inform health systems decision making to achieve epidemic control; one recent study applied machine learning (ML) to aggregate loss to follow-up (LTFU) behavior in people living with HIV [We are using fiscal year 2020 data and calculations according to the U.S. President's Emergency Plan for AIDS Relief (PEPFAR) Monitoring, Evaluation, and Reporting version 2.4, therefore we will refer to interruption in treatment as LTFU. We recognize that PEPFAR is shifting language of LTFU and retention to interruption in treatment and continuation of treatment, respectively] into clusters to examine and describe people living with HIV having similar characteristics and patterns according to their risk profile.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, the real-world application of such analyses using AI technologies often focus on predictive model development, with a limited but emerging evidence-base deploying and scaling the models as effective and sustainable AI solutions in HIV programs. [9][10][11] There are few studies that examine the related use case of advanced analytics to inform health systems decision making to achieve epidemic control; one recent study applied machine learning (ML) to aggregate loss to follow-up (LTFU) behavior in people living with HIV [We are using fiscal year 2020 data and calculations according to the U.S. President's Emergency Plan for AIDS Relief (PEPFAR) Monitoring, Evaluation, and Reporting version 2.4, therefore we will refer to interruption in treatment as LTFU. We recognize that PEPFAR is shifting language of LTFU and retention to interruption in treatment and continuation of treatment, respectively] into clusters to examine and describe people living with HIV having similar characteristics and patterns according to their risk profile.…”
Section: Introductionmentioning
confidence: 99%
“…Hariharan et al (2020) observed that random forest (Figure2) was the most effective ML algorithm for predicting vaccine utilization. Additionally, the authors noted that the model outperformed the conventional technique of vaccination utilization tracking.…”
mentioning
confidence: 97%
“…2,3 With the ongoing global vaccine roll-out, AI-driven insights and applied interventions continue to play a significant role in adaptive and predictive technology. Some applications include tracking COVID-19 mutations and variants to inform vaccine design and development; 4,5 predictive impact modeling for describing which populations and regions to vaccinate to rapidly flatten the curve and end the pandemic; 6 monitoring the supply chain management and vaccine delivery; 7 as well as post-vaccine surveillance to monitor adverse events and track effectiveness. The pandemic has provided opportunities for leveraging the rapidly evolving data and AI technologies to address this public health crisis.…”
mentioning
confidence: 99%